2018
DOI: 10.1186/s12877-018-0894-0
|View full text |Cite
|
Sign up to set email alerts
|

A framework for secondary cognitive and motor tasks in dual-task gait testing in people with mild cognitive impairment

Abstract: BackgroundCognition is a key factor in the regulation of normal walking and dual-task gait assessment is an accepted method to evaluate the relationship. The objective of this study was to create a framework for task complexity of concurrent motor and cognitive tasks with gait in people with mild cognitive impairment (MCI).MethodsCommunity-dwelling people with MCI (n = 41, mean age = 76.20 ± 7.65 years) and cognitively normal controls (n = 41, mean age = 72.10 ± 3.80 years) participated in this study. Gait vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 23 publications
2
59
0
Order By: Relevance
“…the relative time difference between single-and dual-task performances, did not discriminate between any of the groups in the current study. In previous studies, dual-task cost has been found to discriminate between mild AD and healthy controls [46] and between MCI and healthy controls [19,29], and has shown inconsistent results when discriminating between dementia disorders and MCI [18,19], and was not able to discriminate between MCI and SCI [18]. It may be argued that dual-task cost cannot differentiate between transitional diagnoses, because it captures subtle pathological changes and is therefore better considered an indicator of imminent cognitive decline [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the relative time difference between single-and dual-task performances, did not discriminate between any of the groups in the current study. In previous studies, dual-task cost has been found to discriminate between mild AD and healthy controls [46] and between MCI and healthy controls [19,29], and has shown inconsistent results when discriminating between dementia disorders and MCI [18,19], and was not able to discriminate between MCI and SCI [18]. It may be argued that dual-task cost cannot differentiate between transitional diagnoses, because it captures subtle pathological changes and is therefore better considered an indicator of imminent cognitive decline [50].…”
Section: Discussionmentioning
confidence: 99%
“…The recorded data collection consisted of three different TUG tests; first TUGst, followed by TUG while simultaneously naming different animals (TUGdt NA), and finally TUG while simultaneously reciting months in reverse order (TUGdt MB). The choice of the verbal task NA was based on previous research [29,45,46], while to the best of our knowledge MB has not been used as a part of dual-task research [45]. Participants were instructed to execute all TUG tests at their own pace, with the simultaneous performance of the verbal task at a self-selected speed.…”
Section: Clinical Diagnostic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A study revealed that the difficulty level associated with walking while carrying a glass of water on a tray with one hand (a manual motor task) was the same as that associated with walking with the usual gait at a preferred walking speed in cognitively healthy adults. 40 Because gait velocity decrements during a dual task are related to the difficulty of the task, 40 we used a more challenging motor dual task (ie, carrying a tray of water with two hands); as expected, a decrease in gait speed was observed. With arch support, DTCs on both cadence and speed decreased, indicating a decrease in the percentage of loss in motor dual-task performance relative to single-task walking performance.…”
Section: Discussionmentioning
confidence: 87%
“…One approach would be to choose another position that does not suffer from the perceptual conflict and would have a better haptic perception rate. To this, the literature offers connected jackets to communicate non-visual information [40][41][42][43] or the wrist [16]. This new method will have a wider range of applications including spatial orientation and guidance, attention management, haptic guidance, assistance, and better learnability [44,45].…”
Section: Implication Of the Results From This Studymentioning
confidence: 99%